MEMBANGUN KETAHANAN RELEGIUS ANAK MELALUI ACTIVE PARENTAL INVOLVEMENT - Buton, La Husni; Susiati, Susiati; Masniati, Andi; Tuasalamony, Kurniati; Hatuwe, Rahma Satya Masna; Tahir, Saidna Zulfiqar Bin; Tenriawali, A. Yusdianti; Marasabessy, Roos Nilawati (JURNAL ISLAM NUSANTARA, 2020)
The objectives of this study were to 1) determine the behavior of parents in educating children's religiosity; 2) identify children's actions in applying religiosity in society. The location of this research is in Ubung Village, Lilialy District, Buru Regency, because this location is assessed as the role of parents in educating children's religiosity very high and intensively. This research is a qualitative descriptive study. The method in this research is the method of observation with data collection techniques used, namely in-depth interviews, observation, and documentation. The sampling technique used was purposive sampling technique. The results showed 1) parental behavior in educating religiosity in the village of Ubung includes (1) democratic parenting or behavior. In this pattern there are four aspects applied by parents in Ubung Village, namely (a) aspects of affection, (b) aspects of communication, (c) aspects of self-control, (d) aspects of maturity demands; (2) permissive parenting; (3) attachment parenting; (4) authoritarian parenting; (5) helicopter parenting; (6) negligent parenting. 2) As for the children's actions in implementing religiosity in the community in Ubung Village, namely looking happy and happy in their interactions, never learning to control their behavior, having a high sense of care for their surroundings, often less happy, withdrawn, afraid, and less confident When comparing themselves with others, children tend to be afraid of expressing opinions, low self-esteem, and so on.